Pewarisan Budaya Dan Nilai Keislaman Pada Tradisi Sayyang Pattu'du' Oleh Etnis Mandar - Irmayanti; Ita Rodiah (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2024)
The tradition of sayyang pattu’du’ is a celebratory tradition in West Sulawesi by the Mandar ethnic group as an expression of gratitude upon successfully completing the recitation of the Qur'an. This tradition is considered to embody Islamic values passed down from generation to generation. This research aims to analyze values within the culture of sayyang pattu’du’ that may contradict Islamic values. The method used in this research is descriptive qualitative with a field research approach. There were six informants in this study. Data collection was conducted through observation, interviews, and documentation, supported by various scholarly literature. Data analysis involved data reduction, presentation, and drawing conclusions. The research findings indicate that there are certain aspects within the sayyang pattu’du’ tradition that the author considers to be inconsistent with Islamic values, contrary to the intended demonstration of Islamic values through this tradition.